Rangeland condition in the Tembe Traditional Area, Maputaland, KwaZulu-Natal, South Africa - Van Rooyen, M.W. (Margaretha W.), 1950- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.